Deaths of two hospital inpatients poisoned by pilocarpine. Issue 6557 (15th November 1986) - Cordner, S M; Fysh, R R; Gordon, H; Whitaker, S J
Abstract : Two inpatients of one hospital ward died. Pilocarpine poisoning was suspected and subsequently confirmed by analysis of urine. The circumstantial evidence strongly suggested that the food given to the patients in the ward had been adulterated. Police inquiries failed to elicit any further information, and open verdicts were returned at the inquest. Precautions taken subsequently to prevent a similar event--sealing food containers and trolleys--entailed a capital cost of 43, 000 pounds. In addition, food stores were kept locked and tighter control kept on drugs stored in ward pharmacies.